1974
DOI: 10.1002/pen.760140208
|View full text |Cite
|
Sign up to set email alerts
|

Rheological analysis of stabilizing forces in wire‐coating dies

Abstract: A rheological analysis of a wire-coating die is presented. The rheological forces which might play a role in the stability of the wire are estimated. In particular, consideration is given to lateral forces related to the secondary normal stress function acting on the wire which is in an eccentric position, and the hydrodynamic force related to the viscosity function acting on the wire which moves at an angle to the die axis. For the former a simple, yet general, expression was derived by solving the flow probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Bagley and Storey [14] provided numerical solutions for a Newtonian fluid in the form of dimensionless parameters characterizing the wire speed, die dimensions, radial position, shear rate, and melt viscosity. Tadmor and Bird [15] examined the effect of visco-elasticity on the eccentricity of the wire. Using the Criminale-Ericksen-Filbey (CEF) constitutive equation, they concluded that the lateral forces acting on the wire tend to stabilize it into a concentric position.…”
Section: Introductionmentioning
confidence: 99%
“…Bagley and Storey [14] provided numerical solutions for a Newtonian fluid in the form of dimensionless parameters characterizing the wire speed, die dimensions, radial position, shear rate, and melt viscosity. Tadmor and Bird [15] examined the effect of visco-elasticity on the eccentricity of the wire. Using the Criminale-Ericksen-Filbey (CEF) constitutive equation, they concluded that the lateral forces acting on the wire tend to stabilize it into a concentric position.…”
Section: Introductionmentioning
confidence: 99%
“…Aspect ratios varied from 0.002 to 0.03. The detailed description of the experimental device is found in [5]. Several types of experimental fluids were considered: a) Newtonian: Polybutene Oil (Chevron).…”
Section: Methodsmentioning
confidence: 99%
“…Their work dealt mainly with shear ow under both isothermal and non-isothermal conditions. Molten polymers have been noted to exhibit highly elastic behaviour when subject to large deformation [11]. Only recently, numerical techniques have proven capable of reaching solutions for su ciently high and relevant levels of elasticity: some limited attempts include those of References [12] and [17].…”
Section: Background On Wire-coatingmentioning
confidence: 99%
“…Tadmor and Bird [11] considered the problem of a wire travelling on an axis parallel, but not co-linear to the die. Since the wire was centred with a guider before entering the die, and the wire was under high tension, the problem is more ideal than practical.…”
Section: Background On Wire-coatingmentioning
confidence: 99%